204 Effects of sorghum silage kernel processing on intake and apparent total tract digestibility of beef heifers. (30th November 2020) - Podversich, Federico; Roskopf, Sergio; Abdelhadi, Leandro; da Silva, Gleise Medeiros; Tarnonsky, Federico; Fernandez, Federico; Sanchez, Federico; Batista Dubeux, Jose Carlos; Ferraretto, Luiz; DiLorenzo, Nicolas
Abstract: This study evaluated the effect of different kernel processors in terms of nutrient digestibility of whole-plant sorghum silage. Grain sorghum (hybrid ADV1250IG, Advanta Seeds, Irving, TX) was harvested at the hard-dough stage with a Class Jaguar 960 and 930 harvesters, switching the kernel processor to generate the forage material for the three treatments: conventionally processed (CONV), unprocessed (UN), and shredlage processed (SHRED). The material was bagged in three 2.7 m bags and allowed to ferment for 1 mo. Twenty-four black Angus heifers (13 ± 1 mo, 267 ± 10.9 kg of BW) were randomly assigned to treatments (8 heifers/treatment) and allocated to individual pens (36 m 2 ) with access to feed and water. Diets were ad libitum sorghum silage from each respective treatment, plus soybean meal top-dressed at 0.5% of BW. After a 15-d adaptation period, feed and feces were collected for 5 d. Feed was offered once daily, and orts were collected the following day. Fecal samples were collected twice daily and apparent total tract digestibility was determined using indigestible NDF as a marker. Data were analyzed as a completely randomized design using heifer as the experimental unit, and initial BW as a covariate. Dry matter (DM) intake as a percentage of BW (P = 0.09) and NDF digestibility (P = 0.06) tended to differ among treatments, where CONV tended to be lesser than UN (P = 0.08), whereas SHRED was intermediate. Digestibility of DM was affected by treatment (P = 0.05), where UN (71.3%) tended (P = 0.06) to be greater than CONV (67.9%), while SHRED (70.8%) did not differ from any of the treatments (P ≥ 0.12). In conclusion, kernel processing affects nutrient digestibility of sorghum silage. Differences in ruminal kinetics and fermentation parameters, resulting from contrasting particle sizes, grain processing and sorting, may help explain these findings.